2007
DOI: 10.1186/1749-8090-2-54
|View full text |Cite
|
Sign up to set email alerts
|

Length of pressure-controlled reperfusion is critical for reducing ischaemia-reperfusion injury in an isolated rabbit lung model

Abstract: Background: Ischaemia-reperfusion injury is still a major problem after lung transplantation. Several reports describe the benefits of controlled graft reperfusion. In this study the role of length of the initial pressure-controlled reperfusion (PCR) was evaluated in a model of isolated, bufferperfused rabbit lungs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Age !55 years (n = 19) Age <55 years (n = 167) p-value early hyperperfusion of the first implanted graft and, most importantly, controlling reperfusion and ameliorating ischaemia/reperfusion injury to both implanted grafts [13,14]. Therefore, perioperative factors were similar in both groups, excluding the influence of different strategies on the long-term outcome of both groups.…”
Section: Cause Of Death (N = 61) Group a (N = 8) Group B (N = 53) P-vmentioning
confidence: 80%
“…Age !55 years (n = 19) Age <55 years (n = 167) p-value early hyperperfusion of the first implanted graft and, most importantly, controlling reperfusion and ameliorating ischaemia/reperfusion injury to both implanted grafts [13,14]. Therefore, perioperative factors were similar in both groups, excluding the influence of different strategies on the long-term outcome of both groups.…”
Section: Cause Of Death (N = 61) Group a (N = 8) Group B (N = 53) P-vmentioning
confidence: 80%
“…There is exhausting evidence highlighting the importance of controlled organ reperfusion, and the length of controlled reperfusion is critical. [14][15][16][17] In addition, one of the main features in donor organ injury is a significant endothelial leakage. 18 By reducing the blood flow through a predamaged pulmonary vascular bed, fluid extravasation and further impairment of pulmonary function can be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the benefits of controlled reperfusion for early graft function. [15][16][17][18] Additionally, with a routine application of ECMO in LTx, extremely low numbers of reperfusion edema have been reported. 19,20 Because this is especially true for the later time points, the discrepancies between best and worst case scenarios in our study are less profound at t72.…”
Section: Discussionmentioning
confidence: 99%